DETERMINATION OF DIBUTYL PHTHALATE (DBP), BENZYL BUTYL PHTHALATE (BBP) AND BIS (2-ETHYLHEXYL) PHTHALATE (DEHP) IN SOFT PLASTIC TOYS AND THE FIRST SURVEY OF THE BULGARIAN MARKET - Valentina CHRISTOVA-BAGDASSARIAN (Stefan cel Mare University of Suceava, 2017)
Phthalates are a large group of compounds with similar chemical structure widely used as plasticizers for plastics. They can easily be released from the polymer during usage and in this way enter the human body. Their adverse effect on health is known as "phthalate syndrome" and can impact children and adults alike. For children in particular, there is an additional potential risk of exposure to phthalates via toys intended for oral use. The Regulation (EC) No 1907/2006 (REACH) prohibits the use of bis (2-ethylhexyl) phthalate (DEHP), di butyl phthalate (DBP) and benzyl butyl phthalate (BBP) as a substance or constituent of preparations at concentrations higher than 0.1 % in the plasticized material meant to toys and childcare items. The aim of this article is to quantify the content of DEHP, DBP and BBP in soft toys intended for children up to 3 years of age, including toys designed to be placed in the mouth. A method consisting of an extraction procedure of phthalates from polymers, purification of the extract, followed by GC/MS identification and quantification was validated. Three different techniques for phthalates’ extraction (Soxhlet, ultrasonic and vibrator) were compared and the most effective one was chosen.This method was applied to the analysis of DEHP, DBP and BBP in soft toys from the Bulgarian market to establish their compliance with REACH requirements. All the tested toys contained at least one phthalate. Exceedence of the permitted content for DEHP, DBP and BBP (as sume), mainly due to the high levels of DEHP, was observed in several toys from retail.